Inhibition of SLC drug transporter activities by environmental bisphenols - Bruyere, Arnaud; Hubert, Céline; Le Vee, Marc; Chedik, Lisa; Sayyed, Katia; Stieger, Bruno; Denizot, Claire; Parmentier, Yannick; Fardel, Olivier (Toxicology in vitro, 2017)
The plastic component bisphenol A (BPA) is suspected to exert deleterious effects towards human health and targets various cellular and molecular pathways, including activity of ATP-binding cassette drug transporters. The present study was designed to determine whether BPA and some derivatives, like its substitutes bisphenol F (BPF) and bisphenol S (BPS) and the flame retardant tetrabromobisphenol A (TBBPA), may additionally interact with solute carrier (SLC) drug transporters. Activities of the various following SLC transporters were inhibited in a major way (by >60%) by 100μM bisphenols: OCT1 and MATE1 (by BPA and TBBPA), OATP1B1 (by BPA, BPF and TBBPA), OATP1B3 and NTCP (by TBBPA) and OAT3 (by BPA, BPF, BPS and TBBPA); by contrast, activities of other transporters were not impacted (MATE2-K) or were stimulated (notably OCT1 by BPS and OCT2 by BPF). Transporter inhibitions due to bisphenols were concentrations-dependent, with half maximal inhibitory concentrations (IC50) ranging from 0.5μM to 73.5μM. BPA was finally shown to be not transported by OAT3, although inhibiting this transporter in a competitive manner. Taken together, these data indicate that bisphenols interact with SLC transporters, at concentration levels however rather higher than those occurring in humans in response to environmental exposure. •Environmental bisphenols inhibited activities of various SLC drug transporters.•OCT1, MATE1 and OATP1B1 were thus notably targeted by bisphenol A.•Bisphenol A also competitively inhibited OAT3, without however being transported.•High concentrations of bisphenols were however needed for SLC transporter inhibitions.